The Legal Status of Unborn Children as Heirs: A Comparative Study of Civil Law and Islamic Law - Iriyanti; Suriaatmaja, Toto Tohir; Kartono (Sinergi International Journal of Law, 2025)
The purpose of this study is to examine and compare the legal status of children as heirs based on the Civil Code and Islamic Law. The data collection process uses primary legal sources, including the principles and standards that have been set out in documents such as the Civil Code, Islamic jurisprudence, and the Compilation of Islamic Law on inheritance. Additional information is obtained from legal textbooks, academic journals, scientific articles, legal dictionaries, and relevant encyclopedic references. This study illustrates that there are significant differences in the procedures used to transfer inheritance to unborn children.